Perkembangan Smart Distribution Seosoning System Menggunakan Delphi 7 Berbasis Orange Pi - Ratna Gusrianti; Retno Devita; Yogi Wiyandra (Universitas Putra Indonesia YPTK Padang, 2023)
Kitchen seasonings are substances that generally come from aromatic plants which are added to dishes with the aim of flavoring food. Seasoning serves to make food taste better. Delicious or not a food depends on the spices added. Seasoning is made from a mixture of spices through various processing processes. Generally, cooking spices are classified into three groups, namely red, white and yellow main spices. Many types of spices can be made into seasonings, for example coriander, pepper, black pepper. There are various types of spices, so storage in the warehouse requires a place that is suitable for the types of spices. So that suppliers are not confused about storing kitchen spices and if needed they are not confused anymore. The supplier will send the spices according to consumer demand, samples in kilo sizes according to the space provided and there will be no more mistakes. This research was carried out by designing, manufacturing and implementing the process, LCD as an information display, Load Cell as a detector for spices, and speakers providing information in the form of sound covering the microcontroller controlling the process, namely the Orange Pi.